Nanoparticulate CpG Immunotherapy in RAO‐Affected Horses: Phase I and IIa Study. (January 2015) - Klier, J.; Lehmann, B.; Fuchs, S.; Reese, S.; Hirschmann, A.; Coester, C.; Winter, G.; Gehlen, H.
<x xml:space="preserve">Abstract</x> Background Recurrent airway obstruction (RAO), an asthma‐like disease, is 1 of the most common allergic diseases in horses in the northern hemisphere. Hypersensitivity reactions to environmental antigens cause an allergic inflammatory response in the equine airways. Cytosine‐phosphate‐guanosine‐oligodeoxynucleotides (CpG‐ODN) are known to direct the immune system toward a Th1‐pathway, and away from the pro‐allergic Th2‐line (Th2/Th1‐shift). Gelatin nanoparticles (GNPs) are biocompatible and biodegradable immunological inert drug delivery systems that protect CpG‐ODN against nuclease degeneration. Preliminary studies on the inhalation of GNP‐bound CpG‐ODN in RAO‐affected horses have shown promising results. Objectives The aim of this study was to evaluate the clinical and immunological effects of GNP‐bound CpG‐ODN in a double‐blinded, placebo‐controlled, prospective, randomized clinical trial and to verify a sustained effect post‐treatment. Animals and Methods Twenty‐four RAO‐affected horses received 1 inhalation every 2 days for 5 consecutive administrations. Horses were examined for clinical, endoscopic, cytological, and blood biochemical variables before the inhalation regimen (I), immediately afterwards (II), and 4 weeks post‐treatment (III). Results At time points I and II, administration of treatment rather than placebo corresponded to a statistically significant decrease in respiratory effort, nasal discharge, tracheal secretion, and viscosity, AaDO2 and neutrophil percentage, and an increase in arterial oxygen pressure. Conclusion and Clinical Importance Administration of a GNP‐bound CpG‐ODN formulation caused a potent and persistent effect on allergic and inflammatory‐induced clinical variables in RAO‐affected horses. This treatment, therefore, provides an innovative, promising, and well‐tolerated strategy beyond conventional symptomatic long‐term therapy and could serve as a model for asthma treatment in humans.